Laboratory experiments related to marine plastic pollution: a review of past work and future directions - Poulain-Zarcos, Marie; Pujara, Nimish; Verhille, Gautier; Mercier, Matthieu J. (Comptes Rendus. Physique)
Plastic pollution is a very active research topic for a wide variety of scientific disciplines. While existing reviews of plastic pollution in the ocean cover the topic from different disciplinary and interdisciplinary viewpoints, this review addresses the contributions from laboratory experiments towards the geophysical processes important in marine plastic pollution research. We review the laboratory research on the transport, transformations, and origin and fate of marine plastic pollution with recommendations for future research.